Kepraktisan E-Modul Interaktif Berbantuan Canva Pada Materi Ekosistem Yang Harmonis Kelas V Di Sekolah Dasar - I Nyoman Ananta Widiadnya; Putu Yulia Angga Dewi; I Ketut Ngurah Ardiawan (Walada: Journal of Primary Education, 2026)
Abstract: Science and social studies (IPAS) learning under the Merdeka Curriculum demands a contextual, student-centered approach; however, the "Harmonious Ecosystem" material for fifth-grade elementary students is still delivered through conventional teaching materials, making the abstract concept of interrelationships among ecosystem components difficult for students at the concrete operational stage to grasp. This study aims to develop and analyze the practicality of a Canva-assisted interactive e-module on this material. The study employed a Research and Development (R&D) approach using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). Product validity was assessed by three experts in content, media, and language using Aiken's V formula, while practicality was tested through response questionnaires completed by two teachers and seventeen fifth-grade students at SD Negeri 2 Bungkulan. The validity results indicated a "very valid" category for the media (0.86), content (0.88), and language (0.92) aspects. The practicality test yielded an average score of 96% from teachers and 91% from students, both categorized as "very practical," with individual student scores ranging from 86% to 96%. The Canva-assisted interactive e-module proved to be feasible and practical for use in making the abstract concept of ecosystems more concrete, making it a viable digital teaching material alternative for teachers in supporting the implementation of the Merdeka Curriculum. Keywords : Interactive E-Module, Canva, Science and Social Studies (IPAS), Harmonious Ecosystem, Elementary School